Sensory evaluation of high protein enriched Bellamya bengalensis - Bidisha Maiti Mondal; Anupam Maity; Chandrasekhar SM; Ranajit Kumar Khalua (The Bioscan, 2024)
This study evaluates the sensory qualities of high protein-enriched Bellamya (a freshwater snail protein source) in comparison with two commonly used protein supplements, commercial whey protein and soy protein powder. The study examines consumer acceptability across multiple sensory attributes—taste, texture, appearance, and overall acceptability—between the three protein-enriched samples. A trained panel conducted sensory evaluations, and results were analyzed to determine the optimal formulation in terms of sensory preference, aiming to assess Bellamya’s potential as an alternative, high-quality protein source in the market.